Malaysia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Malaysia's well-diversified economy continued to perform well in 2014. Growth accelerated to 5.9 percent, aided by robust domestic private demand and a recovery in exports. Lower energy costs helped contain inflation to 3.1 percent despite the removal of fuel subsidies and increase in electricity tariffs. Growth is expected to moderate to 4.8 percent in 2015. Strong investment momentum should help offset headwinds from continued fiscal consolidation. Lower energy prices will be a drag on oil and gas production but should provide a boost to the large non-oil sector.